1981
DOI: 10.1007/bf01315130
|View full text |Cite
|
Sign up to set email alerts
|

Microtubules and microfilaments in HSV-infected rabbit-kidney cells

Abstract: In rabbit kidney cells infected with strains of Herpes simplex virus producing either cell-rounding or polycaryocytosis. Vinblastine induced paracrystals. This could be shown by phase-contrast- and electron-microscopy. Infections were done under one-step-growth conditions or at low MOI. 90 per cent noninfected cells contained stress fibers as detected by Servablue R250-staining. Shortly after recruitment into polycaryocytes, stress fibres of normal length appearing in criss-cross arrangement can be seen in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
(25 reference statements)
3
17
0
Order By: Relevance
“…The distribution of myosin in the infected cells correlated well with previous reports on the actin-myosin complex in both transformed (Pollack et al, 1975;Weber & Grolschel-Stewart, 1974;Bourguignon & Rozek, 1978) and lyticaUy infected cell cultures (Fagraeus et al, 1978 ;Meyer et al, 1981 ;Heeg et al, 1981 ;Rutter & Mannweiler, 1977). In the case of tubulin, vimentin and keratin, at least two different organization patterns were noted in the infected cells after c.p.e, was well established.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The distribution of myosin in the infected cells correlated well with previous reports on the actin-myosin complex in both transformed (Pollack et al, 1975;Weber & Grolschel-Stewart, 1974;Bourguignon & Rozek, 1978) and lyticaUy infected cell cultures (Fagraeus et al, 1978 ;Meyer et al, 1981 ;Heeg et al, 1981 ;Rutter & Mannweiler, 1977). In the case of tubulin, vimentin and keratin, at least two different organization patterns were noted in the infected cells after c.p.e, was well established.…”
Section: Discussionsupporting
confidence: 89%
“…Microfilament reorganization has been used as one indication of viral transformation of cultures (Pollack et al, 1975). More recently, changes in microfilament bundle patterns have been defined as possibly playing a role in the morphological alterations which occur during lytic infections induced by different viruses (Fagraeus et al, 1978;Heeg et al, 1981;Meyer et al, 1981). Moreover, studies on the formation of polykaryons after infection by the parainfluenza virus, SV5, revealed that thick bundles of both microtubules and intermediate filaments reformed into parallel rows during cell fusion (Wang et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is well known that HSV induces changes in cell morphology, i.e. cytopathic effects, with alterations of the actin cytoskeleton seen late in viral infection [9,15,24]. The most prominent cellular alteration is polykaryocyte formation by syn-virus, in which actin filaments have been implicated [15].…”
Section: Introductionmentioning
confidence: 99%
“…cytopathic effects, with alterations of the actin cytoskeleton seen late in viral infection [9,15,24]. The most prominent cellular alteration is polykaryocyte formation by syn-virus, in which actin filaments have been implicated [15]. If TPA alters actin and its anchorage systems, it is supposed that virus-induced cell fusion would be modified in the presence of TPA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation